Evaluation of electrophysiological characteristics and ventricular synchrony: An intrapatient‐controlled study during His‐Purkinje conduction system pacing versus right ventricular pacing. Issue 7 (3rd May 2022) - Chen, Xueying; Zhou, Xiaolan; Wang, Yanan; Jin, Qinchun; Chen, Yufei; Wang, Jingfeng; Qin, Shengmei; Bai, Jin; Wang, Wei; Liang, Yixiu; Chen, Haiyan; Su, Yangang; et al.
Abstract: Objectives to Background: To compare electromechanical ventricular synchrony when pacing from different sites, including right ventricular apex pacing (RVAP), right ventricular septum pacing (RVSP), His bundle pacing (HBP), left bundle branch pacing (LBBP), and RVSP during unipolar pacing from the ring electrode of LBBP lead (RVSPring ) in each patient and evaluate the correlations between electrophysiological characteristics and ventricular synchrony. Methods: Twenty patients with complete atrioventricular block indicated for dual‐chamber pacemaker implantation were included in the study. Unipolar pacing at different sites, including RVAP,  RVSP,  HBP,  LBBP, and RVSPring, was successively performed in each patient. The pacing characteristics and echocardiogram parameters were collected and compared among intrinsic rhythm and pacing at different sites. Results: Similar to HBP (114.84 ± 18.67 ms), narrower paced QRSd was found in LBBP (116.15 ± 11.60 ms) as compared to RVSPring (135.11 ± 13.68 ms), RVSP (141.65 ± 14.26 ms), and RVAP (160.15 ± 19.35 ms) ( p  < .001). LBBP showed comparable pacing parameters to RVAP or RVSP and was significantly better than HBP, with maintained cardiac function. TS‐12‐SD was significantly improved in LBBP (41.80 ± 20.97 ms) than RVAP (69.70 ± 32.42 ms, p  = .003) and RVSP (63.30.56 ± 32.53 ms, p  = .018) but similar to HBP (51.50 ± 25.67 ms, p  = .283) or RVSPring (57.80 ± 25.65 ms, p  = .198). Among these pacing strategies, negative values of interventricular mechanical delay (IVMD) were only identified in LBBP (−19.25 ± 18.43 ms), significantly different from RVAP (35.00 ± 30.72 ms), RVSP (22.85 ± 22.05 ms), HBP (5.20 ± 18.64 ms), and RVSPring (16.00 ± 26.76 ms (all p  < .05). Using Pearson's analysis, Sti‐LVAT was positively correlated with QRS duration, IVMD, TS‐12‐SD, LVEDV, and LVESV, while a negative relationship could be observed for left ventricular ejection fraction. Conclusions: His‐Purkinje conduction system pacing (HPCSP) achieved better electrical and mechanical synchrony than conventional RV pacing. For interventricular synchrony, only LBBP initiated earlier LV activation than RV, in accordance with the right bundle branch block (RBBB) pattern of paced QRS during LBBP. Sti‐LVAT might be a good parameter correlating with LV systolic function and mechanical synchrony.